Modeling car-sharing membership as a mobility tool: A multivariate Probit approach with latent variables. (July 2017) - Becker, Henrik; Loder, Allister; Schmid, Basil; Axhausen, Kay W.
Highlights: Joint model for ownership of four different mobility tools. Interrelations between the different mobility tools are accounted for. Multivariate approach is substantially more efficient than univariate approaches. Car and GA highly flexible mobility tools attracting affluent and frequent travelers. Car-sharing is used as complement by both season-ticket holders and car-owners. Abstract: Individual travel behavior is to a large extent shaped by the respective portfolio of available mobility tools such as cars, season-tickets or a car-sharing membership. However, the choices of different mobility tools are interdependent and are also affected by individual attitudes. This paper presents an approach to jointly model the choice of four different mobility tools – including car-sharing. Using data from the Swiss transportation micro census of 2005 and 2010, it is shown that car-sharing is used as a supplement to a public transportation-oriented lifestyle, but is also used by car owners. The results further indicate that personal attitudes have a substantial effect on the choice of mobility tools and should therefore be accounted for when modeling such decisions.